2019
DOI: 10.1002/pbc.28134
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of sirolimus in combination with metronomic therapy (CHOAnome) in children with recurrent or refractory solid and brain tumors

Abstract: Background/purpose To determine the maximum tolerated dose, toxicities, and response of sirolimus combined with oral metronomic therapy in pediatric patients with recurrent and refractory solid and brain tumors. Procedure Patients younger than 30 years of age with recurrent, refractory, or high‐risk solid and brain tumors were eligible. Patients received six‐week cycles of sirolimus with twice daily celecoxib, and alternating etoposide and cyclophosphamide every three weeks, with Bayesian dose escalation over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…A total of 146 clinical trials were included in further analysis. Trial descriptions were extracted from registry websites, 53 publications, 8‐63 and 9 abstracts (ASCO website n = 6; results section of websites n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 146 clinical trials were included in further analysis. Trial descriptions were extracted from registry websites, 53 publications, 8‐63 and 9 abstracts (ASCO website n = 6; results section of websites n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Two different areas of research can be identified: mCHT as maintenance treatment in different pediatric cancer [ 109 ] Metronomic combination of different chemotherapy drugs [ 110 , 111 ] mCHT in combination with other drugs [ 112 , 113 , 114 ] …”
Section: Metronomic Chemotherapy: Areas Of Noveltymentioning
confidence: 99%
“…Qayed et al [ 112 ] explored the role of sirolimus in a Phase 1 trial in combination with celecoxib BID, and alternating etoposide and CTX administered every 3 weeks in 18 patients younger than 30 years of age with recurrent, refractory, or high-risk solid and brain tumors. The study established the recommended dose for sirolimus at 2 mg/m 2 .…”
Section: Metronomic Chemotherapy: Areas Of Noveltymentioning
confidence: 99%
“…Besides, multiple pathways and genes associated with metabolic and environmental stress have been recovered, suggesting that autophagy modulation might be a new strategy to fight glioblastoma. Several autophagy inhibitors and its derivates have been extensively studied in vitro in several groups of glioblastoma patients [190,191]. Although testing them in vitro using various glioblastoma cells clearly shows the benefits for anticancer therapy, the precise mechanism of their therapy remains unclear.…”
Section: Glioma Stem Cells: the Undercover Resistance Mediatorsmentioning
confidence: 99%